Biological Importance of Flavonoid Bavachinin in the Medicine: Perspectives of Medicinal Importance, Pharmacological Activities and Analytical Techniques - Patel, Kanika; Patel, Dinesh K. (Natural Products Journal, The, 2023)
Backgrounds: Phytochemicals are an important class of natural compounds present in vegetables, herbs, fruits, and seeds. Phytochemicals have been used in medicine for the treatment of human disorders in the form of drugs, medicine, and Nutraceuticals. Flavonoid class secondary metabolites were found to be present in medicinal plants and some food materials derived from plants. Flavonoid class phytochemicals have beneficial health aspects and numerous pharmacological activities in the medicine. Psoralea corylifolia has been widely used in medicine for the treatment of skin diseases, including vitiligo, alopecia areata, leukoderma, and psoriasis. More than 90 different types of phytocompounds have been separated and isolated from Psoralea corylifolia. Bavachinin is a flavonoid class phytochemical, found to be present in the seeds of Psoralea corylifolia. Bavachinin possesses anti-bacterial, anti-oxidative, anti-inflammatory, α-glucosidase and nitric oxide inhibitory potential. Methods: Scientific data on bavachinin have been collected from different literature databases such as Google, Google Scholar, PubMed, Science Direct and Scopus in the present work and analyzed to know the biological importance of bavachinin. Scientific research data on bavachinin have been collected in the present work for their medicinal importance, pharmacological activities and analytical aspects. Further, all the collected scientific data have been separated into different sub-sections i.e., Medicinal importance, pharmacological activities and analytical aspects of bavachinin. Detailed pharmacological activity data of bavachinin have been analyzed in the present work to know the therapeutic potential of bavachinin in medicine. Analytical data of bavachinin have been collected and analyzed in the present work to know the biological importance of bavachinin in modern medicine for the standardization of Psoralea corylifolia. Results: Literature data analysis of different scientific research works revealed the biological importance of flavonoids in medicine. Flavonoid class phytochemicals have anti-inflammatory, antioxidant, anti-viral, anti-cancer and anti-ageing properties in medicine. Scientific data analysis revealed the effectiveness of bavachinin in cancer, blood glucose, Alzheimer's disease, Parkinson's disease, inflammation, immune system, T cell differentiation, oxidative damage and enzymes. However, therapeutic efficacy, metabolism, biotransformation, pharmaceutical product development and pharmacokinetic parameters of bavachinin have also been discussed in the present work. Analytical data signified the importance of modern analytical tools for the separation, isolation and identification of bavachinin. Conclusion: Scientific data analysis of different research work revealed the biological importance and therapeutic benefit of bavachinin in medicine.
Keywords: inflammation